EP814 TGFβ pathway activation is a predictor of progression free and overall survival in advanced high-grade serous ovarian cancer according to the surgical aggressiveness and rate of cytoreduction of different oncologic centers. (1st November 2019) - Ceppi, L; Grassi, T; Romualdi, C; Di Lorenzo, P; Palazzi, S; Biagioli, E; Garbi, A; Paracchini, L; Landoni, F; Aletti, GD; Colombo, N; Fruscio, R; et al.
Abstract : Introduction/Background: The activation of TGFβ pathway in advanced stage high-grade serous ovarian cancer (HGSOC) has been found to be related to short progression free survival (PFS) and overall survival (OS). miRNA181a-5p was found to be a proxy of TGFβ activation. This prognostic role has been identified only in cohorts with low surgical complexity, we evaluated 2 cohorts with different surgical approaches. Methodology: Series of HGSEOC from two centers (European Institute of Oncology, Milan, Cohort1 ; San Gerardo Hospital, Monza, Cohort2 ) were analyzed for clinical features and miRNA quantification to test their prognostic value using a Cox-proportional hazard regression model. Results: 118 and 84 patients were included, respectively. Cohort1 versus Cohort2 was composed of similar FIGO stages, higher upper abdominal disease spread (UAD) (P<0.001), higher complexity score (CS) of 6.7±2.4 and 3.5±1.7 (P<0.001) and lower residual tumor (P<0.001). Cohort1 compared to Cohort2 was associated with a lower number of events of PFS and OS (P<0.0012). An optimized threshold of miR181a-5p expression to segregate patients according to their prognosis was identified (miR-low and miR-high): for Cohort1 no threshold was reached; for Cohort2 a threshold segregated PFS of 20.9 v. 9.6 months (P:0.0008) and OS of 60.3 v. 23.3 months (P:0.0008), respectively. In multivariate analysis, no significance was observed for miR-high in Cohort1. For Cohort2, miR-high was related to worse PFS (P:0.0002), and OS (P:0.007). Conclusion: miR181a-5p was observed as a prognostic biomarker in HGSEOC in Cohort2, -less aggressive surgery-, instead no prognostic role was observed in Cohort 1 -aggressive surgery-. This question-generating analysis suggests that TGFβ activation, a proxy of tumor aggressiveness, might be withdrawn by an aggressive surgical approach. A prospective validation of miR181 role is needed, the translational ancillary study of the TRUST trial (NCT # 02828618) may answer this question. Disclosure: Nothing to disclose.